2021
DOI: 10.3390/brainsci11030391
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms in Oxidative Stress-Related Genes and the Risk of a Stroke in a Polish Population—A Preliminary Study

Abstract: The present preliminary case-control study was undertaken to detect the potential association of six single nucleotide polymorphisms (SNPs) in oxidative stress-related genes: SOD2 (c.47T > C; rs4880), CAT (c.-89A > T; rs7943316), GPX4 (c.660T > A; rs713041), NOS1 (g.117803515C > T; rs1879417) and NOS2 (c.1823C > T; rs2297518 and c.-227G > C; rs10459953) and the occurrence of a stroke. The SNPs were determined using the TaqMan® Allelic Discrimination Assay in 107 patients with strokes and 107 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…Notably, the heterozygous AV16 genotype seems to represent the better conditions for optimal enzyme activity of mitochondrial Mn-SOD, given the highest frequency observed in our study cohorts, that is in line with findings from several studies carried out in Italian and Caucasian populations ( 23 , 37-41 ). Most importantly, these same studies, and several others not cited here, suggested that the SOD2 AA16V (rs4880) polymorphism may have an impact on acute and chronic oxidative-related damage, and increase the susceptibility to various oxidative stress-related pathological conditions, such as pregnancy complications, cardio- and cerebrovascular disorders, cancer, glaucoma, diabetes ( 37 , 38 , 40-43 ), and even accelerates telomere shortening with age ( 39 ).…”
Section: Discussionsupporting
confidence: 65%
“…Notably, the heterozygous AV16 genotype seems to represent the better conditions for optimal enzyme activity of mitochondrial Mn-SOD, given the highest frequency observed in our study cohorts, that is in line with findings from several studies carried out in Italian and Caucasian populations ( 23 , 37-41 ). Most importantly, these same studies, and several others not cited here, suggested that the SOD2 AA16V (rs4880) polymorphism may have an impact on acute and chronic oxidative-related damage, and increase the susceptibility to various oxidative stress-related pathological conditions, such as pregnancy complications, cardio- and cerebrovascular disorders, cancer, glaucoma, diabetes ( 37 , 38 , 40-43 ), and even accelerates telomere shortening with age ( 39 ).…”
Section: Discussionsupporting
confidence: 65%
“…The selected studies reported data related to GPX4 (rs713041) SNP linked to nineteen diseases; these included breast cancer [ 16 , 17 ], colorectal cancer [ 35 , 36 ], prostate cancer [ 20 , 37 ], laryngeal cancer [ 19 ], lung cancer [ 19 ], pre-eclampsia [ 38 , 39 ], hypertension [ 40 ], ischemic stroke [ 41 ], endometriosis [ 22 ], recurrent miscarriage [ 42 ], pregnancy loss [ 43 ], Graves’ disease [ 23 ], Hashimoto disease [ 23 ], acute pancreatitis [ 44 ], Alzheimer’s disease [ 24 ], depression [ 25 ], multiple sclerosis [ 26 ], type 2 diabetes mellitus [ 45 ] and Kashin-Beck disease [ 46 ]. Regarding demographics, from the twenty-one reports, one study was performed on Arabs [ 45 ], two reports on Russians [ 42 , 43 ], one report on Caucasian Americans [ 36 ], one report on South Americans [ 24 ], five reports on Asians, Han Chinese population [ 22 , 23 , 38 , 39 , 46 ], and the other eleven reports on Europeans [ 16 , 17 , 19 , 20 , 25 , 26 , 35 , 37 , 40 , 41 , 44 ]. Genotyping was carried out by different methods, two reports using real-time PCR [ 19 ], one KASPar [ 35 ...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding demographics, from the twenty-one reports, one study was performed on Arabs [ 45 ], two reports on Russians [ 42 , 43 ], one report on Caucasian Americans [ 36 ], one report on South Americans [ 24 ], five reports on Asians, Han Chinese population [ 22 , 23 , 38 , 39 , 46 ], and the other eleven reports on Europeans [ 16 , 17 , 19 , 20 , 25 , 26 , 35 , 37 , 40 , 41 , 44 ]. Genotyping was carried out by different methods, two reports using real-time PCR [ 19 ], one KASPar [ 35 ], two reports MassArray [ 23 , 37 ], four reports PCR-RFPL [ 42 , 43 , 44 , 46 ] and the remaining twelve reports using TaqMan assay [ 16 , 17 , 20 , 22 , 24 , 25 , 26 , 36 , 38 , 39 , 40 , 41 , 45 ]. The characteristics, genotyping methods, sample size and genotype frequency of the twenty one reports are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, according to data provided by NCBI dbSNP, 56,540 SNPs in NOS1 have been registered, while NOS2 has 16,601 various polymorphisms. Numerous polymorphisms, occurring within this gene [especially g.117803515 C > T— NOS1 (rs1879417) and c.1823C > T— NOS2 (rs2297518)], play an essential role in the development mechanism of various diseases, including Fanconi anemia, depression, stroke, gastric, and urinary bladder cancer 35 , 37 40 . The first analyzed polymorphism in our study is g.117803515 C > T— NOS1 (rs1879417) localized in the intron on chromosome 12, at position 12q24.22.…”
Section: Discussionmentioning
confidence: 99%